2008
DOI: 10.1194/jlr.m800015-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Increased methionine sulfoxide content of apoA-I in type 1 diabetes

Abstract: Cardiovascular disease is a major cause of morbidity and premature mortality in diabetes. HDL plays an important role in limiting vascular damage by removing cholesterol and cholesteryl ester hydroperoxides from oxidized low density lipoprotein and foam cells. Methionine (Met) residues in apolipoprotein A-I (apoA-I), the major apolipoprotein of HDL, reduce peroxides in HDL lipids, forming methionine sulfoxide [Met(O)]. We examined the extent and sites of Met(O) formation in apoA-I of HDL isolated from plasma o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
35
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 59 publications
5
35
1
Order By: Relevance
“…These findings suggest that oxidation of two of the three methionines within apoA-I causes a dramatic change in the conformation of the lipid-bound protein, with the N-terminal region becoming much more solvent exposed than in its native, unoxidized form (87). Recently Brock et al (88) reported that the methionine sulfoxide content of apoA-I was more abundant in the HDL of patients with type-1 diabetes, a disease for which cardiovascular events are a more significant complication, than in control patients.…”
Section: Methionine Oxidation Alters N-and C-termini Of Lipid-free Anmentioning
confidence: 99%
“…These findings suggest that oxidation of two of the three methionines within apoA-I causes a dramatic change in the conformation of the lipid-bound protein, with the N-terminal region becoming much more solvent exposed than in its native, unoxidized form (87). Recently Brock et al (88) reported that the methionine sulfoxide content of apoA-I was more abundant in the HDL of patients with type-1 diabetes, a disease for which cardiovascular events are a more significant complication, than in control patients.…”
Section: Methionine Oxidation Alters N-and C-termini Of Lipid-free Anmentioning
confidence: 99%
“…For example, methionine sulfoxide [Met(O)], has been detected in circulating HDL of humans (20), and reactive intermediates are implicated in impairment of LCAT activity (21)(22)(23)(24)(25). Moreover, it was recently shown that the Met(O) content of apoA-I is elevated in human type 1 diabetes, a disorder strongly associated with increased levels of oxidative stress (26). Because a single Met residue, Met-148, lies in the LCAT activation domain of apoA-I (27), we investigated the role of Met oxidation in the loss of LCAT activity that occurs when MPO oxidizes apoA-I.…”
mentioning
confidence: 99%
“…Simi-larly, apoA-I containing methionine residues 86 and 112 as MetO (hereafter referred to as apoA-I 132 ) has been detected in circulating HDL, and is present at increased concentrations in subjects with a genotype associated with increased coronary artery disease (16). Moreover, it was recently shown that the MetO content of apoA-I is elevated in human type 1 diabetes (17), a disorder commonly associated with increased oxidative stress (18).…”
mentioning
confidence: 99%